Trehalose Induced regulations in Physio-biochemical attributes of Helianthus annuus under Lead stress (Plant Bulletin, 2023)
Heavy metal is a substantially severe abiotic environmental stress that is rising in many regions of the world. Current climate change circumstances and rapid industrialization increased heavy metal accumulation in soil and water. Overall, worldwide agricultural production decreased. Trehalose, a well-known plant growth regulator, is crucial in plants' responses to a variety of abiotic conditions. The Morpho-physiological and biochemical parameters were analyzed in hydroponic research to identify the possible role of trehalose in alleviating heavy metal lead acetate stress in sunflower (Helianthus annuus L.) crops. In the sole and mixed form, two Pb(C2H3O2)2 (Control and 30 micron) and one trehalose (50 M L-1) levels were used, and a half-strength Hoagland solution was used as a nutritional medium. The current study found that heavy metal stress had a significant negative impact on plant growth (root and shoot length), fresh and dry biomass, and plant water relations, as well as poor plant water relations, membrane stability, chlorophyll content, and antioxidant enzyme activities such as superoxide dismutase (SOD), peroxide (POD), ascorbate peroxide (APX), and catalase (CAT). MDA and H2O2 are the stress markers reduced by the application of trehalose. Exogenous treatment of trehalose, on the other hand, significantly mitigates the detrimental effects of metal toxicity by altering plant physiology, enhancing water relations, and providing robust antioxidant defense against heavy metal lead acetate stress. The findings of this study provide a new dimension to scientists' understanding of the beneficial usage of trehalose in plant science and offer up new research opportunities.
Keywords: Metal toxic Environment; antioxidant activities; Trehalose; Sunflower; Antioxidant Defense; Lead; RWC